Strategi Pengembangan Bisnis Supplier Ikan Beku Hasil Tambak di PT Mekar Berseri Sempurna Gresik - Mohammad Hammas Ainurroyyan El Falih; Vembri Aulia Rahmi; Aries Kurniawan (eCo-Buss, 2024)
This study employs qualitative methods to identify internal and external factors through observations, interviews, and documentation. The analysis results of internal and external factors were analyzed using the SOAR matrix (strengths, opportunities, aspirations, results). The practical knowledge gap in the context of research on frozen farmed fish supplier business development strategies refers to the lack of understanding or application of relevant innovative marketing strategies to improve the competitiveness and sustainability of the business. While there is existing theory and research on marketing and business development, further research is needed to identify specific tactics and approaches that frozen farmed fish suppliers can implement. The purpose of this study is to investigate the business growth strategies of PT. Mekar Berseri Sempurna's frozen aquaculture fish suppliers. The expansion of the frozen fish industry is associated with shifts in consumer preferences. These changes facilitate the simplification of household activities in preparing food. Hence, there is a growing need for food that is healthy, safe, nutritious, practical, and saves processing time. The research employs a descriptive qualitative analysis method, utilizing data collection techniques such as interviews, observations, and documentation. This increasing demand provides great opportunities for frozen fish food companies. The results of this study are (1) Creating market mapping to determine potential demand (2) Collaborating with other companies (3) Certifying and improving product quality standards